AIDS in Africa : a manual for physicians - Piot, Peter (WHO, 1992)
HIV and AIDS are a major health problem in many parts of Africa. Many physicians and other health workers are having to cope daily with a disease for which they have had little or no training. Most published information n the features of HIV infection relates to Europe and North America. WHO have now brought together information that has previously been available only in specialist journals, providing a comprehensive description of the clinical manifestations of HIV infection in Africa, as well as guidelines on the management of patients. It represents a guide in the fight against AIDS in Africa.
Keywords: Acquired Immunodeficiency Syndrome; epidemiologie; dermatovenerologie; Afrika; Epidemiologic Studies; infekční lékařství; epidemiologické studie; AIDS; Africa; sociální lékařství